Role of Anticonvulsants in the Management of AIDS Related Seizures - KIRMANI, BATOOL F.; Mungall-Robinson, Diana (Frontiers in Neurology, 2014)
Seventy percent of the AIDS patients have neurological complications. Seizures are one of the complications and can occur at any stage. Seizures can be life–threatening and treatment with anticonvulsants is warranted. The therapeutic dilemma occurs in this case because of the interactions between the anticonvulsants, especially the first generation anticonvulsants, with antiretroviral agents resulting in significant side effects including toxicity. The non-availability of second-generation anticonvulsants and cost constraints further limit the choices for the physicians. In this mini-review, we discuss the management of AIDS related seizures with emphasis on the drug-drug interactions between anticonvulsants and antiretroviral agents. We will also address the future directions and the need for prospective studies with second-generation anticonvulsants.